2023
DOI: 10.21833/ijaas.2023.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Surviving amidst pandemic: Indonesian Islamic microfinance experience

Abstract: The purpose of this study is to investigate the Indonesian Islamic microfinance institutions' (IMFIs) condition, and their strategies to survive and to explore their contribution during the pandemic by combining and synthesizing the result of all previous studies. To achieve that goal, this research uses a systematic literature review method by mining all data available which in addition makes this paper different from other previous works. This enables us to provide a deeper, broader, and more comprehensive u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…*The BPS (Central Bureau of Statistics) survey in 2020 found that Indonesia's economic growth in the fourth quarter of 2020 experienced a contraction of -2.07%. This data explains that the country's economy as a whole is declining (Athief et al, 2023). Through the Ministry of Tourism, the government has made a breakthrough in the Indonesian tourism sector, namely halal tourism.…”
Section: Introductionmentioning
confidence: 91%
“…*The BPS (Central Bureau of Statistics) survey in 2020 found that Indonesia's economic growth in the fourth quarter of 2020 experienced a contraction of -2.07%. This data explains that the country's economy as a whole is declining (Athief et al, 2023). Through the Ministry of Tourism, the government has made a breakthrough in the Indonesian tourism sector, namely halal tourism.…”
Section: Introductionmentioning
confidence: 91%
“…This facilitates the process of mainstreaming and applying the concepts of religious moderation at UIN Malang (Rahman et al, 2023). In contrast to Salahuddin College for Islamic Studies (STAIS) Pasuruan, not all tertiary institutions have had access to institutional improvement and human resource development to fulfill their responsibility in mainstreaming religious moderation values (Athief et al, 2022).…”
Section: Introductionmentioning
confidence: 99%